Design and implementation of training module for control liquid level on tank using PID method based PLC. Issue 3 (April 2020) - Yahya, S; Jadmiko, S W; Wijayanto, K; Tahtawi, A R A
Abstract: Process control is widely used in various industries to maximize production, maintain desired quality levels, product safety and make the process more economical. Control that is generally used in industry is to control liquids, such as controlling the level, flow, pressure, and temperature of the liquid using the Proportional-Integral-Derivative (PID) method, the PID controller attempts to correct errors between the measured process variables and the desired set-point by calculation and then issue actions corrective which can be arranged according to the process. In the past, most PID controllers were based on microcontrollers, but now Programmable Logic Controller (PLC) can also operate PIDs with analog function control because PLC speeds and capabilities have increased. To meet the needs of student competence in process control following industry demands, especially the use of PLC with the PID Method, students need to be given knowledge and skills. One way is the availability of training modules that can grow their enthusiasm and skills when they learn. This paper presents the design and implementation of PLC Omron CP1H based process control training modules that can be used by students to study liquid level control in tanks with PLC-based PID methods. Based on the test results when the plant is disturbed, the system response obtained by the PID method is a 15 second settling time, 10.9% undershoot, and a steady-state value of 14.6 cm or ± 97.3% of the 15 cm setting value.